PENGEMBANGAN KAIN TENUN CEPUK SEBAGAI PENDUKUNG DAYA TARIK WISATA BUDAYA DI NUSA PENIDA - Lanovia Amir, Firlie (Jurnal Master Pariwisata (JUMPA); Volume 04, Nomor 02, Januari 2018DO - 10.24843/JUMPA.2018.v04.i02.p12, 2018)
Bali has fairly well-known for its cultural woven fabrics such as tenun cepuk woven fabric of Tanglad Village, Nusa Penida, Klungkung District. The study assess the potential of cepuk as well as determines strategies and programs that can be applied to develop it as a means of supporting cultural tourism. This study is using a qualitative descriptive approach to measure the variables, and SWOT matrix to explain the data in the formulation of strategies and programs. From the data processing, four strategies can be formulated. Those strategies can be used to increase the welfare of the people of Nusa Penida especially Tanglad Village and also develop a sustainable cultural tourism. The research is expected to be used as a reference in making policies by the government to develop tourism in Nusa Penida as well as for the community to be able to develop the potential of the Cepuk woven fabric.